Phenotypic evaluation of two transgenic potato varieties for control of tecia solanivora (2012)
Eight genetically modified potato lines with cry1Ac gene from Bacillus thuringiensis of the Colombian varieties Diacol Capiro and Parda Pastusa that show high resistance to Tecia solanivora in the laboratory were evaluated under greenhouse conditions. The following agronomic traits were evaluated: plant height, growth habit, canopy structure, number of stems per plant, flowering, form and size of the mini-tubers, skin texture, skin color, pulp color, presence of abnormalities, and experimental performance. It was established that at least one of the transgenic lines studied has great potential for further study, bearing no morphological variability with respect to the unmodified control line.